Caracterización agromorfológica y productiva de Mora (Rubus glaucus Benth) en tres zonas de la provincia Bolívar - Cáceres Bonilla, Santiago Fabian (2017)
The research "Agromorphological and productive characterization of blackberry (Rubus glaucus Benth) in three agroecological zones of the Bolivar Province was developed at the State University of Bolivar, Faculty of Agricultural Sciences, Agricultural Engineering Degree, the objectives were: To characterize agromorphologically and productively (Rubus glaucus Benth) in three agroecological zones of the Bolivar Province, the specific objectives were: To select orchards with greater productivity in the agroecological zones producing blackberry of the Province of Bolívar; Identify and select plants with productive and quality characteristics; Characterize in situ each of the selected plants. The proposed methodology was the characterization of the phenotypic variability of blackberry orchards in the three agroecological zones of the Bolivar province: Capilluco, Chillanes and Guantug Cruz. Measurements were applied to a sample of 15 plants per zone. Measurement variables were applied to the plant: crown diameter, vigor of the plant, total number of main, secondary and tertiary stems, number of production centers by secondary stem, tertiary; Leaf length per secondary and tertiary branch; Leaf diameter per secondary and tertiary branch. In the fruit the variables were evaluated: number of fruits by production centers, fruit weight by secondary and tertiary branch, yield, fruit length by secondary and tertiary branch, fruit diameter by secondary and tertiary branch, titratable acidity, soluble solids, Firmness, color and shape of the fruit. Finally the phytopathological variables were evaluated: incidence and severity of Botrytis, Oídios, Peronospora, descending wilt, damage by aphids, mites, cutzo and borer. The zone with greater productivity predominated over the area of Capilluco in which is established as an average of 6.42 kg per plant; Followed by the Chillanes area with 5.47 kg and the Guantug cross zone with 3.95 kg. The plants with the best productive characteristics correspond to the area of Capilluco and in relation to quality the areas of Guantug Cruz and Chillanes show better results of the evaluation of the variables of investigation in the delay.